Cost Comparison Among Punctate Midline Myelotomy, Intrathecal Pain Pump, and Spinal Cord Epidural Stimulator. (16th November 2020) - Aljuboori, Zaid; Meyer, Kimberly S; Sharma, Mayur; Ball, Tyler; Nauta, Haring J.W
Abstract: INTRODUCTION: Chronic refractory pain can be detrimental to the patients' health and the economy of the healthcare system. Invasive pain procedures can be valuable tools to manage these patients. We present a cost analysis of punctate midline myelotomy (PMM), spinal cord stimulator (SCS), and intrathecal pain pump (ITPP) in patients with chronic pain at our institution. METHODS: A retrospective chart review was performed for patients with chronic pain who underwent one of three invasive pain procedures (PMM, SCS, or ITPP) at our institution. We included patients >18-year-old and with chronic pain resistant to conventional pain medication protocols. We excluded patients with previous operations of the same type. We recorded patients' pain type and procedure characteristics as well as cost data. We used the Wilcoxon rank-sum and one-way analysis of variance to compare the means for three groups with a significance level set to P < .05. RESULTS: A total of 9 patients with chronic pain refractory to conventional medical management were identified, with 3 patients in each of the 3 treatment groups. The mean age was 53, 39.3, and 50.7 years for the SCS, PMM, and ITPP groups, respectively. The SCS was placed in patients with failed back syndrome, while PMM was for patients with chronic non-malignant visceral pain. The ITPP was placed in two patients with chronic visceral cancer pain and one patient with chronic somatic cancer pain. The mean length of stay was 1, 3.6 ± 0.6, 15 ± 5.6 days for the SCS, PMM, and ITPP, respectively. The mean procedure cost was (105, 234, 71, 087, and 79, 333) for SCS, PMM, and ITPP, respectively. The comparative analysis showed that PMM and ITPP incurred a lower procedure cost in comparison to SCS (79, 333 vs 105, 234, P -value <0.05), (71, 087 vs 105, 234, P -value <.05), respectively. Procedure cost between PMM and ITPP (71, 087 vs 79, 333 P -value = .2), were not significantly different, although this comparison did not include additional costs incurred from any pre-op treatment trial, increased length of stay, outpatient maintenance costs typical for both SCS and ITPP. Patients' characteristics, hospital LOS, and procedure-related cost and complications. Group Age (years) Gender Indication LOS (days) Complications Procedure charges SCS 49 M Failed back syndrome 1 None 124, 640 49 M Failed back syndrome 1 None 96, 717 61 M Failed back syndrome 1 None 94, 343 PMM 28 F Chronic visceral pain 4 None 66, 498 37 F Chronic visceral pain 3 None 65, 498 53 F Chronic visceral pain 3 None 81, 972 ITPP 39 F Visceral cancer pain 20 None 82, 000 53 M Visceral cancer pain 14 None 75, 000 60 F Somatic cancer pain 10 None 80, 603 Abbreviations: SCS; spinal cord stimulator, PMM; punctate midline myelotomy, ITPP; intrathecal pain pump. Results of data analysis Mean SD ITPP vs SCS PMM vs SCS PMM vs ITPP SCS 105, 234 16, 848 z score P -value z score P -value z score P -value PMM 71, 087 8, 863 -1.9 0.04 -1.9 0.04 -1.09 0.2 ITPP 79, 333 3, 786 Abbreviations: SCS; spinal cord epidural stimulator, PMM; punctate midline myelotomy, ITPP; intrathecal pain pump. CONCLUSION: The care for patients with chronic refractory pain can be costly, and ablative pain procedures can be cost-effective in comparison to conventional medical management. Among the 3 pain procedures discussed in this report, PMM is the most cost-effective as it obviates the need for efficacy trials, implant device costs, medication refills, maintenance cost, and complication management cost.